HUBUNGAN BEBERAPA PARAMETER KEGEMUKAN DENGAN USIA MENARCHE PADA SISWI DI SMP NEGERI 1 SUMBER, KABUPATEN CIREBON - Dian Fajriyah Pangestika; Apoina Kartini; Martha Irene Kartasurya (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Menarche age tends to be earlier in recent years. This trend could be related to the increase of nutrition status. The research aimed to know the correlation between obesity parameters (mid-upper arm circumference, waist circumference, body fat, body mass index) and age of menarche in junior highschool student. This research used a cross sectional approach. The subject of this research were 65 junior highschool students of SMPN 1 Sumber, Cirebon who were selected by stratified random sampling method. Data were obtained by interviews. MUAC and waist circumference measured by tape, Body fat percentage measured by Bioelectrical Impedance Analysis (BIA), and BMI calculated based on weight and height measurement data . Data were analyzed by pearson product moment and spearman rank tests. The result showed that the mean age of menarche was 11,1±0,74 years, mean MUAC was 23,2±3,01 cm, mean waist circumference is 69,1± 8,71 cm, mean body fat percentage was 26,3±6,17 %, and mean BMI was 20,8±4,27 kg/m2. There were correlations between MUAC (r=-0,273, p=0,028), body fat percentage (r=-0,273, p=0,028), BMI (r=-0,335 p=0,006) and the menarche age. There was no correlation between waist circumference and menarche age (p=0,196). The mean menarche age in SMP Negeri 1 Sumber was normal (10-14 years old). The student who has the higher obesity parameters experienced the menarche age earlier.